Negative effect of feeding with high energy diets on testes and metabolic blood parameters of male Japanese quails, and positive role of milk thistle seed - Ceribasi, S.; Turk, G.; Ozcelik, M.; Dogan, G.; Ceribasi, A. O.; Mutlu, S. Iflazoglu; Simsek, U. G. (Elsevier Science Inc, 2020)
In this study, it was aimed to investigate the changes in testicular tissue and cell count, testicular oxidative stress and some metabolic blood parameters of male broiler Japanese quails fed with high energy diet and milk thistle (Silybum marianum) seed. One hundred-twenty male 15-day-old Japanese quail chicks were divided into 4 equal groups with 30 each. The applications in each group were repeated 3 times with 10 animals each. Control group was fed with basal diet. Milk thistle seed group was fed with diet including 1% milk thistle seed. High energy diet group was fed with high energy diet including 10% corn syrup. High energy diet + milk thistle seed group was fed with high energy diet including 10% corn syrup along with 1% milk thistle seed. The feeding period in all groups was 35 days. When the quails reached 50 days old, a total of 48, 12 from each group (4 from each replication) were euthanized and blood samples and testes were collected. Compared with the control group, significant increases in body weight, serum cholesterol and glucose level, aspartate aminotransferase activity and testicular malondialdehyde level; however, significant decreases in serum testosterone level, testicular glutathione peroxidase activity, counts of round and elongated spermatid and sperm as well as histopathologically, significant decreases in seminiferous tubular diameter and seminiferous epithelium thickness, and marked disorganization in germinal cells were determined in quails fed with high energy diet. It was observed that almost all of the disturbances in testicular tissue, cell number, oxidant-antioxidant balance and metabolic blood parameters caused by feeding with high energy diet were significantly prevented by supplementation of milk thistle seed to the diet with high energy. On the other hand, alone milk thistle seed and high energy diet + milk thistle seed administrations decreased body weight in comparison to control and high energy diet groups. As a result, feeding with high energy diet causes disturbances in testes of male quails by affecting liver metabolic functions and testicular oxidant-antioxidant balance, but milk thistle seed addition to diet plays a protective role. (C) 2019 Elsevier Inc. All rights reserved.
Keywords: High energy diet; Milk thistle seed; Oxidative stress; Metabolic blood parameters; Testis